Symbolism in oriental arts: mythical birds in Buddhist & Hindu arts - Zekrgoo, Amir Hossein (MATN Publishing, Iran Academy of Art, Tehran, 1971)
The book is the 3rd volume of a series under compilation. Each volume is devoted to a certain symbol (animal, plant, human, gestures and postures, tools, etc.) within the religious traditions of the East. The present volume is complemented with some 39 images (including 30 color plates and 9 line drawings) and a glossary of technical terms.